A multinational cross-sectional study on the awareness and concerns of healthcare providers toward monkeypox and the promotion of the monkeypox vaccination - Swed, Sarya; Alibrahim, Hidar; Bohsas, Haidara; Jawish, Nagham; Rais, Mohammed Amir; Nasif, Mohamad Nour; Hafez, Wael; Sawaf, Bisher; Abdelrahman, Ahmed; Fathey, Sherihan; Atef Ismail Ahmed Ibrahim, Ismail; Almashaqbeh, Sondos Hussein Ahmad; et al. (Frontiers in Public Health, 2023)
Background The aim of this study was to explore potential healthcare workers' (HCWs) concerns about the monkeypox virus in order to create practical solutions to manage this disease. Methods Online cross-sectional research was conducted in 11 Arabic countries (Egypt, Saudi Arabia, Yemen, Syria, Libya, Algeria, Tunisia, Iraq, Palestine, Jordan, and Sudan) from 2 August 2022 to 28 December 2022. Results Approximately 82% of respondents felt the need to acquire further information. The acceptability of the vaccine against monkeypox has been indicated by more than half of the participants (54.5%). Furthermore, we state that 45% of the participants are knowledgeable about the monkeypox virus, and 53.1% of the participants have never been affected with COVID-19 before are more worried about COVID-19 than about monkeypox. Participants diagnosed with COVID-19 were 0.63 times less likely to worry about monkeypox than those who were not diagnosed with COVID-19. A greater willingness to get the monkeypox vaccination was seen among the age group 21–30 years (42.4%) compared to the other age groups. Conclusion Most healthcare professionals have a moderate knowledge of the monkeypox virus. Furthermore, they demonstrated a low willingness to get the vaccination against the monkeypox virus.